LEA proteins and ABA signaling: reciprocal regulation in stress adaptation - Hao, Cuihong; Zhan, Xinxin; Guo, Ning; Liu, Jing; Cui, Dayong (Frontiers in Plant Science, 2025)
Challenging environmental conditions are major factors that severely affect plant growth and limit agricultural productivity. To mitigate these stresses, plants have evolved various adaptive mechanisms. Among these, Late Embryogenesis Abundant (LEA) proteins play a pivotal role in responding to abiotic stresses and participate in a reciprocal regulatory network with the abscisic acid (ABA) signaling pathway. However, the precise molecular mechanisms underlying this reciprocity and the full composition of this network require systematic integration. This review synthesizes recent advances to propose a novel “ABA-LEA feedback loop” model and presents a comprehensive analysis of the classification into seven groups, structural features, molecular functions and mechanisms by which LEA proteins contribute to plant stress resistance. Special emphasis is placed on the intricate interplay between LEA proteins and the ABA signaling pathway, encompassing both the ABA-dependent regulation of LEA expression and the reciprocal feedback exerted by LEA proteins on ABA signaling through mechanisms that influence ABA homeostasis and signaling. By synthesizing evidence for this reciprocal regulation, this review establishes a novel feedback loop model that redefines LEA proteins as active modulators rather than passive effectors in stress signaling, offering new theoretical targets for breeding stress-resilient crops.